2014
DOI: 10.1111/mmi.12498
|View full text |Cite
|
Sign up to set email alerts
|

The 4‐cysteine zinc‐finger motif of the RNA polymerase regulator DksA serves as a thiol switch for sensing oxidative and nitrosative stress

Abstract: We show that thiols in the 4-cysteine zinc-finger motif of DksA, an RNA polymerase accessory protein known to regulate the stringent response, sense oxidative and nitrosative stress. Hydrogen peroxide- or nitric oxide (NO)-mediated modifications of thiols in the DksA 4-cysteine zinc-finger motif release the metal cofactor and drive reversible changes in the α-helicity of the protein. Wild-type and relA spoT mutant Salmonella, but not isogenic dksA-deficient bacteria, experience the downregulation of r-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 62 publications
6
88
1
Order By: Relevance
“…Several of those effects that could affect persister formation include inhibition of catalase activity (Brown, 1995), alteration of DksA activity (Henard, et al, 2014), and formation of peroxynitrite through reaction of NO with superoxide (Brunelli, et al, 1995). Since oxidative stress can increase persister levels (Vega, et al, 2012; Wu, et al, 2012) and NO impairs catalase activity, we treated an E. coli strain devoid of catalases (Δ katE Δ katG ) with DPTA at 4 h of growth, and measured type I persistence at 24 h. We observed that NO reduces type I persister levels of Δ katE Δ katG to a similar extent as wild type (Supplementary Figure S5A), which indicated that inhibition of catalase activity by NO does not explain the phenomenon described here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of those effects that could affect persister formation include inhibition of catalase activity (Brown, 1995), alteration of DksA activity (Henard, et al, 2014), and formation of peroxynitrite through reaction of NO with superoxide (Brunelli, et al, 1995). Since oxidative stress can increase persister levels (Vega, et al, 2012; Wu, et al, 2012) and NO impairs catalase activity, we treated an E. coli strain devoid of catalases (Δ katE Δ katG ) with DPTA at 4 h of growth, and measured type I persistence at 24 h. We observed that NO reduces type I persister levels of Δ katE Δ katG to a similar extent as wild type (Supplementary Figure S5A), which indicated that inhibition of catalase activity by NO does not explain the phenomenon described here.…”
Section: Resultsmentioning
confidence: 99%
“…NO is a critical antimicrobial used by the human immune system (Hibbs, et al, 1988), and exogenous administration of NO to infection sites using a number of different delivery mechanisms has produced promising results (Friedman, et al, 2011; Jones, et al, 2010; Robinson, et al, 2014; Sulemankhil, et al, 2012; Sun, et al, 2012) This molecule with diverse functions easily diffuses through the bacterial membranes and reacts with iron-sulfur clusters, superoxide, and oxygen, whereas its oxidized forms damage thiols, DNA, and residues on proteins (Robinson, et al, 2014). This reactivity provides NO with an ability to inhibit or disrupt a diverse set of enzymes and regulatory proteins, which include catalases, respiratory cytochromes, and bacterial reductases (Brown, 1995; Brunelli, et al, 1995; Henard, et al, 2014; Mason, et al, 2009). Such pleotropic effects lead to a complex relationship between NO and antibiotic tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of recombinant TrxA-6His or TrxA C32A C35A-6His to GST-SsrB was analyzed as described previously (Henard et al, 2014). Briefly, 1 nmol of GST-SsrB proteins were incubated with 200 µl of Glutathione-Sepharose 4B beads (BioWorld, Dubin, OH) at 4°C for 2 h, washed with 20 bed volume of 50 mM Tris-HCl, pH 7.5, and then incubated with 2 nmole of TrxA-6His or TrxA C32A C35A-6His proteins at 4°C for 2 h with agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Full-length TrxA and a C-terminal SsrB fragment encompassing residues 137–212 expressed as GST fusions from pGEX6P1 (GE Healthcare Biosciences, Fairfield, CT) were purified as described previously for DksA (Henard et al, 2014). Where indicated, 25 µM recombinant SsrB was treated with 250 µM H 2 O 2 for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In some bacterial pathogens, DksA proteins are critical for bacterial virulence (20)(21)(22)(23)(24). It was recently proposed that Salmonella DksA may act as a sensor for reactive oxygen and nitrogen species due to its redox-active thiols (25). Of the two DksA-like proteins present in Rhodobacter sphaeroides, only one was shown to regulate the stringent response and to be necessary for photosynthetic growth and utilization of exogenous amino acids (19).…”
mentioning
confidence: 99%